Desenvolvimento e caracterização de filmes poliméricos de amido de milho nativo e modificado com incorporação de fibras de bagaço de cana e óleos vegetais. - Carmo, Karina Palmizani do (2016)
A few years ago, several studies have been conducted to transformatio n of raw matter into renewable biodegradable materials, since it is necessary to rethink consumption and rationalize the use of packaging derived from synthetic polymers. Among these raw materials can be detached corn starch produced worldwide, with low cost and high potential for biodegradability. In this paper, aiming a possible application in biodegradable packaging, starch polymeric films were developed using native corn starch with the incorporation of 1 to 4% of fibers sugarcane bagasse from industrial wastes, 2.5, 5 and 10% of castor oil, and 2.5, 5% epoxidized soy bean oil, and modified corn starch films with the incorporation of 1 to 3% fibers sugarcane bagasse, and 2.5, 5 % of epoxidized soybean oil. Some mechanical and thermal analysis for characterization of the films were made. The mechanical p roperties were analyzed by tensile test in Dynamic-Mechanical Thermal Analysis (DMTA) equipment. Among the films tested in tension, they stood the native corn starch films that have the best tensile strength results (1.05 MPa) and elongation at break (77.66%), followed by the native starch containing film 3% fiber (0.81 MPa) and native starch films containing 2.5% epoxidized soybean oil (58.55%). The fractured samples were analyzed by Scanning Electron Microscopy (SEM). Thermal an alysis of all kinds of developed films were made by Differential Scanning Calo rimetry (DSC), Thermogravimetric Analysis (TGA) and Thermogravimetric Analysis Derivative, where the DSC curves showed higher thermal stability for native starch films containing castor oil and epoxidized soybean, in which the thermal decomposition was observed between 270 and 291 o C, being higher than the temperatures of other films , and four stages of degradation for these films, and the others had only three stages of degradation. Native starch films with incorporation o f 3% fiber and 2.5% epoxidized soybean oil were buried in soils incubated for completion of the biodegradability test, and analysis of the emissions o f CO2, CH4, and N2O were performed by gas chromatography, it was possible to observe high CO2 emission rates in the first month of incubation for all films. After 90 days, the films were dug up, and the polymer matrix was completely biodegraded.